Correlation between pain, functional disability, and core endurance in individuals with chronic low back pain according to Saliba’s Postural Classification System - Saleh Elemam, Rania; Ahmed Abdelmegeed, Mohamed; Saad Soliman, Elsadat; Ahmed Soliman, Mohamed Omar; Abdelkader, Nasr Awad (SPORT TK-EuroAmerican Journal of Sport Sciences, 2025)
This study aimed to investigate the correlation of the pain intensity, function disability and core endurance in patients with chronic mechanical low back pain (CMLBP) classified according to Saliba’s postural classification system (SPCS). A total of 60 patients with age ranged from 20-50 years with CMLBP were recruited and randomized into one of the six postural classification groups (10 patients per group). The visual analog scale (VAS) and Oswestry disability index (ODI) were used to measure pain severity and functional disability respectively. Core endurance tests were used to measure core muscles endurance. Pain intensity significantly correlated with function disability in vertical/posterior and anterior/anterior group (r=0.724, p<0.05), while negative correlation existed between pain and core endurance in vertical /posterior group (p<0.05). Furthermore, among CMLBP patients, there were significant positive correlations between pain and function disability (p<0.05), and negative correlations between pain and core endurance (p<0.05), as well as functional disability and core endurance (p<0.05). Pain and functional disability seemed to be highly correlated in vertical/posterior group and negative correlation existed between pain and core endurance in the same group. While among CMLBP patients, pain is strongly associated with functional disability, while both pain and functional disability are inversely related to core endurance, particularly in the vertical/posterior group.